Analysis of lower limb during squat activity using surface electromyography - Ardhi Mardiyanto Indra Purnomo; Lu Jian Qiang; Catur Supriyanto (Universitas Negeri Malang, 2023)
The purpose of this research is to discuss and analyze the extent of the influence of using the bosu ball for squat activities on the lower limb. This research will use a quantitative and descriptive research approach. Surface electromyography will be used to measure different squat positions between 900 and 1400. The measurement compares the squat position without a bosu ball with the squat position using a bosu ball. The results of the surface electromyography recording on muscle activity at 900 on the four muscles indicate that the Rectus Femoris (RF) muscle experienced an increase in the percentage of 18.33%, the Vastus Medialis Oblique (VMO) was 77.92%, the Biceps Femoris (BF) was 24.88%, and the Semitendinosus was 79.63%. Meanwhile, on the 1400 muscle activity, the Rectus Femoris (RF) muscle increased by 31.58%, the Vastus Medialis Oblique (VMO) by 20.19%, the Biceps Femoris (BF) by 28.07%, and the Semitendinosus by 42.93%. This study concludes is that differences in muscles will certainly provide different results as well. In the squat activity at an angle of 900, it shows that the most dominant muscle is the Semitendinosus and the Vastus Medialis Oblique (VMO), while in the squat activity at an angle of 1400, it shows that the most dominant muscle is the Semitendinosus and the Rectus Femoris (RF). So, from the squat angle position, some muscles have their own roles and functions, with the Vastus Medialis Oblique (VMO) muscle having the most dominant result.